Cultural Relations between Germany and Iran and its Impacts on Intellectual Movement in Iran - Nejad, Ahmad Fazli; Andish, Abdol Rasul Kheir; Akbari, Abed (Journal of History Culture and Art Research, 2017)
Cultural diplomacy is one of the tools of public diplomacy that governments are trying to attract people from those countries before attracting other governments; among different types of modern diplomacy, including public diplomacy, media diplomacy, and educational diplomacy, cultural diplomacy has a special significance. During the Qajar era, the German government began a consistent and expansive cultural activities in many countries, including Iran, by understanding the international structure affected by the two powers of Russia and the United Kingdom, as well as the proper understanding of the power of cultural diplomacy. In this paper, we try to answer the following questions: Why did the German government, contrary to its rivals in Iran, the British and Russian governments, define their foreign policy on the basis of a cultural approach? How has this cultural relationship affected the Iranian intellectual community? In response to these questions, we can state the following assumptions: “The German government is aware of the fact that in traditional societies such as Iran, cultural diplomacy based on religious feelings and religious intolerance is higher than any political and economic motive, and that this type of diplomacy is not confronted with the opposition of the two powers of Russia and Britain”. “Iranian-German cultural associations have been influential both on Iranian intellectual activists and those acting with religious backgrounds and those with stronger nationalist tendencies”.